Copiotrophic Bacterial Traits Increase With Burn Severity One Year After a Wildfire - Adkins, Jaron; Docherty, Kathryn M.; Miesel, Jessica R. (Frontiers in Forests and Global Change, 2022)
Wildfire and burn severity influence soil microbial communities during post-fire recovery. If post-fire differences in microbial communities affect soil carbon (C) pool dynamics, altered microbial communities could influence the transition of forests from C sources to C sinks during ecosystem recovery. For example, fire may change the abundance of copiotrophic and oligotrophic bacteria, influencing the kinetic rates of soil C pools due to differences in C-acquisition strategies and nutrient requirements. We assessed differences in soil bacterial communities and soil C pool kinetics one year after a wildfire in a mixed-conifer forest in northern California, USA. We determined whether differences in bacterial communities and soil C pools were related to copiotrophic versus oligotrophic life history strategies. Specifically, we assessed bacterial community oligotrophy versus copiotrophy based on phyla relative abundances and predicted 16S gene copy numbers. We then determined whether these life-histories were correlated with C pool kinetic rates. We further determined whether C degradation metabolic pathways predicted using PICRUSt2 were related to C pool kinetics. We found that copiotrophic bacteria exhibited greater abundance in burned areas than unburned areas, evidenced by increases in 16S rRNA gene copy number and by taxonomic classifications. Furthermore, the abundance of predicted metabolic pathways associated with fast-cycling C compounds increased with severity, including carbohydrate, alcohol, and amine degradation pathways, suggesting increased copiotrophic metabolic strategies. In contrast, the abundance of metabolic pathways of slow-cycling aromatic C compounds did not change, indicating oligotrophic metabolic strategies did not increase. The kinetic rate of the active C pool was positively related to the copiotrophic metabolic pathway of alcohol degradation, and negatively related to oligotrophic pathways like aromatic compound degradation. The links between C pool kinetics and phylum-level life-strategy classifications were ambiguous. Overall, our results suggest that metabolic life-strategies are related to soil C pool kinetics and could have short- and long-term impacts on soil C persistence during post-fire recovery. In the short-term, increased copiotrophy could increase soil C efflux via rapid cycling of labile C pools. However, over the longer-term lower prevalence of oligotrophic strategies could allow aromatic compounds associated with pyrogenic C to accumulate, increasing stable soil C stocks.